Slope stability monitoring in opencast coal mine based on wireless data acquisition system-a case study - Dorthi, Kumar; Ram Chandar, K (International Journal of Engineering and Technology, 2018)
Real time monitoring of slope failures is necessary to maintain the stability of slopes in open cast mines. A 3-level structure of Wireless Data Acquisition System (WDAQ) is developed for real time monitoring of slope deformation and analysis of data. In this paper, a case study is presented in a large opencast coal mine. Deformation in the slopes with slope angles of 49o, 53o, 58o, 64o, 68o and 70o is monitored over old underground workings. The deformation caused due to the external load like movement Heavy Earth Moving Machinery (HEMM). Maximum deformation was 1.57mm for slope angle of 70o. It can be observed that the deformation increased with increased slope angle. This paper also describes that the validation of data based on WDAQ with the conventional method of monitoring as well as numerical modeling. The data obtained using WDAQ is in close to other two methods. The variation is around 11%.Â